(untitled) (REMUNOM, 2025)
Heart failure (HF) can be defined as the inability of the heart to maintain a cardiac output proportional to the metabolic demand of the body or when it only does so at the expense of an increase in its filling pressures. The decrease in output may be due to impairment of systole or diastole or both, with one of them predominating, depending on the specific etiology (functional or structural changes in the heart) and the time of evolution, resulting in the nosological entity HF (signs and symptoms). Systolic dysfunction due to deficit in myocardial contractility is manifested by a decrease in left ventricular ejection fraction (LVEF) and diastolic dysfunction by ventricular filling failures due to reduced capacity to accommodate blood in the cavities, whether at rest or during physical activity. HF is a complex and heterogeneous syndrome, which makes both case identification and patient categorization challenging in epidemiological studies. LVEF is often considered a phenotypic marker of clinical value, as it reflects both the underlying pathophysiological mechanisms and the likely response to treatment. The objective of this study is to report and understand the challenges that impact the quality of life of a patient with heart failure with reduced ejection fraction (HFrEF). The study methodology will be a clinical case with an exploratory literature review with qualitative approaches.